2006
DOI: 10.1007/11926078_49
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of the Web Ontology Landscape

Abstract: Abstract. We survey nearly 1300 OWL ontologies and RDFS schemas. The collection of statistical data allows us to perform analysis and report some trends. Though most of the documents are syntactically OWL Full, very few stay in OWL Full when they are syntactically patched by adding type triples. We also report the frequency of occurrences of OWL language constructs and the shape of class hierarchies in the ontologies. Finally, we note that of the largest ontologies surveyed here, most do not exceed the descrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 11 publications
2
33
0
Order By: Relevance
“…While our conclusions provide a better understanding of the current state of the Semantic Web (complementary with the conclusions of other similar studies [5,8,10,19,34]), they could further benefit the research community as follows. First, we consider them as a proof that a task based evaluation is feasible and useful, thus supporting the hypothesis of the paper.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…While our conclusions provide a better understanding of the current state of the Semantic Web (complementary with the conclusions of other similar studies [5,8,10,19,34]), they could further benefit the research community as follows. First, we consider them as a proof that a task based evaluation is feasible and useful, thus supporting the hypothesis of the paper.…”
Section: Discussionsupporting
confidence: 68%
“…We conclude in Section 5 with a number of observations about the status of the Semantic Web that support our hypothesis and are complementary to findings provided by similar studies of online ontologies [5,8,10,19,34].…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…Third, as SWRL and SPARQL have different levels of expressivity and scalability, it is interesting to compare their performance. For a more in depth discussion of these semantic web technologies, we refer to [27].…”
Section: Step 1: Identification Of Context Typesmentioning
confidence: 99%
“…through analyzing the Linking Open Data dataset. Wang, et al [23] surveyed nearly 1,300 ontologies and analyzed their expressiveness, the use of OWL constructs, the shape of class hierarchy, etc. Tummarello, et al [22] found that …”
Section: Related Workmentioning
confidence: 99%